Harmoni Lintas Agama Masyarakat Tengger - Mohamad Ali Hisyam; Wan Zailan Kamarudin Wan Ali (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
This paper attempts to closely portray interreligious harmony, especially between Muslim and Hindu community in Tengger, East Java. Tengger community are ingrained with their own culture and practicing their unique tradition. Through symbolic-interactionist approach, this paper supposes that this reality represents a cultural process which is simultaneously and flexibly flowing and growing. In the name of brotherhood and humanity, Tengger people are running their daily activities, discounting subjective differences among them. Sociologically, they are focusing on facing the reality as objective necessities where the self and the other are mutually understanding and complementing each other. In this regard, they have improved the way of interaction, from saya-and-mereka perspective to kami-andkita approach. Social activities and religious/cultural rites symbolically become communicative device of inter-relation among the people. Muslim and Hindu harmony in this community denotes multicultural interaction that entails social involvement of members of community. Tengger people, as an animal symbolicum, strive to construct, expand and (re)interpret the symbols for building harmony.